Maternal and foetal outcome in second stage caesarean section: a prospective study - Sharma, Shuchi; Dogra, Poojan; Sharma, Reena; Bhardwaj, Suraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Caesarean section is the most commonly performed abdominal operation in women all over the world. Caesarean sections during the second stage labour accounts for approximately one fourth of all primary caesareans. Caesarean section at full cervical dilatation is technically difficult and is associated with increased trauma to the lower uterine segment and adjacent structures, as well as increased haemorrhage and infection. Aims and objectives were to determine the indications, maternal and foetal morbidity associated with caesarean section in the second stage of labour. Methods: This prospective study included consecutive 50 cases of caesarean section deliveries conducted in second stage of labor for singleton live pregnancies at term. The data collected in the study was analyzed in terms of maternal demographics, indications of caesarean section, intra-operative and postoperative complications and neonatal outcomes. Results: In our series of 50 deliveries, arrest of descent of fetal head due to malposition was the most common indication of caesarean section accounting for 74% and average procedure time was 45-70 minutes. PPH (62%) was the most common complication. Bladder injury was found in 14% cases. Neonatal outcome variables like APGAR<3 at 5 minutes, respiratory distress and neonatal death were observed in 7, 26 and 2 deliveries respectively. Conclusions: Women undergoing cesarean section in second stage of labour are associated with increased maternal and fetal morbidity. They require special care and hence operation should ideally be performed and supervised by an experienced obstetrician. A proper judgement is required to take a decision for caesarean section at full cervical dilatation.